Петровская Балка – памятник заключительного этапа каменного века - Паламарчук, С.В. (Материалы по археологии Северного Причерноморья, 2019)
Поселение (стоянка) конца каменного века Петровская Балка, расположенное в верховьях эпонимной балки на южной окраине г. Симферополя, открыто в 1985 г. В 1985, 1986, 1990 и 1991 гг. на нем автором были произведены раскопки и получен значительный материал, однако, по ряду причин личного характера, публикация его тогда не состоялась. Тем не менее сохранившиеся архивные материалы: отчеты, описи, фотографии, чертежи, таблицы рисунков многих предметов коллекции и пр., ныне позволили вновь обратиться к этому памятнику с целью его первичной публикации. The paper presents an overview of the archaeological researches in the framework of the exploration of late prehistoric occupation in the structural slope (cuesta) in the Inner ridge of the Cremean mountains. The fieldwork (1985–1991) focused on the settlement of Petrovskaya Balka The most significant findings and results include: there were open and fixed the remains of the site of hunter-gatherers with the beginnings of agriculture in the Late Neolitic period with a maximum recorded for the Petrovskaya Balka at 4670 ± 80 14C BP (Кі – 2981), calibration: 3620–3354 BC. Structures of the cultural layer registered stable character of occupation. A specific feature of the site is the presence of a large number of snail shells in this layer along with other finds. The flint assemblage (7.300 units) represents a broad spectrum of specimens of tools and waste. The ceramics collection (near 800 units) contains two classes of pottery – ornamented and non- ornamented, but both of them were closed in time. Petrovskaya Balka refers to the Mountainous Crimea culture. Archaeozoological evidense have suggested that in the economy of the inhabitants was dominated by hunting and picking up snails. The set of fauna and mollusk chracterise the climatic stage of the end of Atlanticum and the beginning of the subboreal from IV to III thousand BC.